2022
DOI: 10.1108/ir-04-2022-0102
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid obstacle avoidance method for mobile robot navigation in unstructured environment

Abstract: Purpose Wheeled mobile robots (WMR) are the most widely used robots. Avoiding obstacles in unstructured environments, especially dynamic obstacles such as pedestrians, is a serious challenge for WMR. This paper aims to present a hybrid obstacle avoidance method that combines an informed-rapidly exploring random tree* algorithm with a three-dimensional (3D)-object detection approach and model prediction controller (MPC) to conduct obstacle perception, collision-free path planning and obstacle avoidance for WMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…MPC improved the safe distance between the robot and obstacles. In simulation experiments, this method helped the robot to avoid obstacles successfully [10]. MPC can also be used in path optimization for AUVs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…MPC improved the safe distance between the robot and obstacles. In simulation experiments, this method helped the robot to avoid obstacles successfully [10]. MPC can also be used in path optimization for AUVs.…”
Section: Related Workmentioning
confidence: 99%
“…The real-time control effect of the method is poor [9] Accurately estimating errors in open-loop problems The application scope of the method is limited [10] Improved safety distance between robots and obstacles…”
Section: Table 1: Summary Of References Referencementioning
confidence: 99%
“…The results indicated that this method met the application requirements of wheeled robots in unstructured environments. Additionally, the study optimized the model predictive controller by incorporating the distance between obstacles and robots, ensuring a safe distance [ 9 ]. A. Alhalabi et al introduced a drift compensation technology for a wheeled robot platform based on multi-sensor fusion.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, the IMU acceleration measurement values are transformed, gravity vector is removed after transforming to the PLOS ONE world coordinate system, and the pose of the wheeled robot can be calculated. In the encoder preprocessing, the velocity and slip factor φ k of the wheeled robot are included, as expressed in Eq (9).…”
Section: Plos Onementioning
confidence: 99%
“…We are not the first to try to combine sample-based planners with MPC. Zhou et al [28] run a variation of the sample-based planner Informed RRT* [29] to generate shortest-distance paths avoiding obstacles, and opt to track this path directly with MPC under the assumption that it will be collision free. Similar to this work, Al-Moadhen et al [30] use Batch Informed Trees (BIT*) as the sample-based motion planner with the addition of a B-Spline smoothing post-processing step to generate kinematically feasible paths to be tracked with MPC.…”
Section: Model Predictive Controlmentioning
confidence: 99%